Lacanian literary criticism and the topological unconscious. Issue 1 (2nd January 2019) - Greenshields, Will
ABSTRACT: This essay challenges a certain trend in the Anglo-American reception of Lacan – namely, the tendency to either explicitly or implicitly section off his work on the literary from his attempts to present, in a non-metaphorical fashion, the mathematised structure of the psychoanalytic subject. It is, I argue, only when proper account is taken of Lacan's topologisation of the unconscious that the precise nature of Lacan's reading methodology – offered as an alternative to 'applied psychoanalysis' – becomes clear. The essay begins by noting the choice Lacan made in the 1970s to align the unconscious not with the symbolic (language and law) but with the real and outlines why the latter concept is best presented as a topological ex-sistence. Following an examination of the two topological qualities that define the psychoanalytic subject (the unlocalisable twist and the irreducible hole), the essay concludes with an explanation of the dense arguments proffered in two little read écrits on the subject of psychoanalytic literary criticism ('Lituraterre' and 'Preface to the Work of Robert Georgin') and articulates why the relation between the unconscious and literature is not akin to that between cause and effect but instead concerns a shared structural real.